Social identity and place-based dynamics in community resilience building for natural disasters: an integrative framework - Farny, Steffen; Dentoni, Domenico (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
Natural disasters such as wildfires, hurricanes, and droughts pose fundamental challenges to ecosystems and the communities that inhabit them, hence triggering and even forcing community renewal over time. In preparation for future disasters, communities need to develop integrated disaster responses, that is, responses that combine scripted action (such as disaster plans and procedures) and emergent action (such as improvised network formation and spontaneous acts of solidarity). Although scripted action can be planned by authorities, emergent action requires deeper work on the social identity underpinnings of a community. Therefore, we conduct an integrative review to synthesize insights from social identity and social-ecological resilience studies into a framework that prefiguratively explains why some communities likely better recover from natural disasters than others. In essence, we argue that community identity salience, disaster frames, and memory work interact in shaping resilience building. Our work thus integrates social identity into local understandings of community resilience by explaining place-based identity dynamics that shape community adaptation and transformation in preparation for disasters.
Keywords: Community Identity Salience; Community Resilience; Disaster Frame; Integrative Review Method; Memory Work; Resilience